Beyond the Personalization–Privacy Paradox: Privacy Valuation, Transparency Features, and Service Personalization. Issue 2 (3rd April 2017) - Karwatzki, Sabrina; Dytynko, Olga; Trenz, Manuel; Veit, Daniel
Abstract: Digital services need access to consumers' data to improve service quality and to generate revenues. However, it remains unclear how such services should be configured to facilitate consumers' willingness to share personal information. Prior studies discuss an influence of selected individual traits or service configurations, including transparency features and service personalization. This study aims at uncovering how interactions among individuals' privacy valuation, transparency features, and service personalization influence their willingness to disclose information. Building on information boundary theory, we conducted an experimental study with 286 participants on a data-intense digital service. In contrast to our expectation, we found no indication that providing transparency features facilitates individuals' information disclosure. Relative to the personalization–privacy paradox, individuals' privacy valuation is a strong inhibitor of information provision in general, not only for personalized services. Personalization benefits only convince consumers who exhibit little focus on privacy. Thus, service providers need to align their service designs with consumers' privacy preferences.